2018
DOI: 10.1002/hbm.23994
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure differences between Chinese and Caucasian cohorts: A comprehensive morphometry study

Abstract: Numerous behavioral observations and brain function studies have demonstrated that neurological differences exist between East Asians and Westerners. However, the extent to which these factors relate to differences in brain structure is still not clear. As the basis of brain functions, the anatomical differences in brain structure play a primary and critical role in the origination of functional and behavior differences. To investigate the underlying differences in brain structure between the two cultural/ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 68 publications
9
61
2
Order By: Relevance
“…The regions showed obvious anatomical differences that were mainly located in the sensorimotor regions and several highorder function regions such as the dorsal attention and language-related regions (e.g., Broca's and Wernicke's areas). These regional differences were quite similar to the previous multicultural brain studies in which Chinese adults showed significantly thinner cortical thickness in the premotor cortex, inferior frontal gyrus and supramarginal gyrus (Chee, et al, 2011); smaller cortical volume; and larger surface areas in the bilateral superior and medial prefrontal and the bilateral orbitofrontal gyrus (Tang, et al, 2018) compared with Western. These consistent regional differences are reasonable because the high-order functions related to cultural and educational factors such as the language abilities have developed prominently in children at school age.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The regions showed obvious anatomical differences that were mainly located in the sensorimotor regions and several highorder function regions such as the dorsal attention and language-related regions (e.g., Broca's and Wernicke's areas). These regional differences were quite similar to the previous multicultural brain studies in which Chinese adults showed significantly thinner cortical thickness in the premotor cortex, inferior frontal gyrus and supramarginal gyrus (Chee, et al, 2011); smaller cortical volume; and larger surface areas in the bilateral superior and medial prefrontal and the bilateral orbitofrontal gyrus (Tang, et al, 2018) compared with Western. These consistent regional differences are reasonable because the high-order functions related to cultural and educational factors such as the language abilities have developed prominently in children at school age.…”
Section: Discussionsupporting
confidence: 88%
“…However, the existing children brain templates are constructed mostly based on Western pediatric populations (Fonov, et al, 2011;Oishi, et al, 2018;Richards, et al, 2016;Sanchez, et al, 2012;Wilke, et al, 2008;Wilke, et al, 2002), with a typical case being the widely used National Institutes of Health pediatric atlases (NIH-PD) (Fonov, et al, 2011). These existing brain templates are not ideal for use in Chinese pediatrics studies , since Chinese adults and children have unique neuroanatomical features in the brain size and shape as compared to Western people (Bai, et al, 2012;Liang, et al, 2015;Tang, et al, 2010;Tang, et al, 2018;Xie, et al, 2015). Different growth trajectories of some brain structures between Chinese and North American children have also been reported (Guo, et al, 2007;Xie, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is uncertain which factors cause variations in cognitive processes. It is reasonable to assume that they are based on the interplay of multiple factors that include sociocultural, environmental and biological influences, such as philosophical tradition [1], parent-child interaction [3,4], socioeconomic status and personal wealth [5], literacy [6], the complexity of the physical environment [7], differences in the anatomical and functional aspects of the central nervous system [8,9], or means of subsistence [10,11]. Probably the most used explanatory factors for the existence of cultural differences in cognition are the cultural syndromes of individualism and collectivism (independent and interdependent self, respectively) [12,13].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…Previous studies have reported significant cortical surface morphology differences (e.g., gray matter cortical volume, cortical surface area, and cortical thickness) between Chinese and Caucasian brains (Chee, Zheng, Goh, Park, & Sutton, ; Kochunov et al, ; Tang et al, ). Visual assessment of our results showed that the sCN200 cortical surface templates are shorter in length and slightly greater in height than the sUS200 cortical surface templates, which is consistent with previous studies that reported differences between Chinese and Caucasian volumetric measures (Tang et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 96%